The Effect of Silver Nanoparticles Manufacturd by Lactobacillus Bacteria on Some Bacterial Isolates Causing Gingivitis: Pengaruh Nanopartikel Perak yang Diproduksi oleh Bakteri Lactobacillus terhadap Beberapa Isolat Bakteri Penyebab Radang Gusi - Faris, Huda Natiq; Ghyadh, Bushra Ali; AL-Muswie, Rana Talib (Indonesian Journal on Health Science and Medicine, 2024)
A Silver nanoparticles is considered to be able to kill multi resistant isolates due to its little dynamic effect on Microorganisms. The Gram-positive bacterium Lactobacillus bulgaricus was used in this investigation to manufacture NPs and evaluate their efficacy against certain pathogenic strains (Staphylococcus aureus, Staphylococcus mutans). For the production of nanoparticles, pure cultures of Lactobacillus bulgaricus were obtained from patients with gingivitis and dental caries and cultivated in "nuterient agar" broth. After centrifuging the Lactobacillus bulgaricus culture, cell-free supernatant containing silver ions was used. aqueous samples, and use a well-agar spread test to assess their antibacterial properties against bacterial strains obtained from the mouths of patients with dental caries and periodontitis. The disc diffusion method is used to create an antibiotic profile that targets certain harmful microorganisms. The main signal of the synthesis and characterization of the silver nanoparticles was a change in hue to a light yellow.The combination is dark brown in hue, as determined by visual and ultraviolet absorption spectroscopy. The results showed that AgNPs generated by Lactobacillus bulgaricus have antibacterial efficacy against certain types of bacteria. Compared to the studied antibiotics, our results indicate that Lactobacillus bulgaricus has a tremendous potential for creating AgNPs that are very powerful against bacteria. Red blood cells are not cytotoxically affected by silver nanoparticles at concentrations of 1.5 mg/ml Highlights: Silver nanoparticles show antimicrobial potential against resistant bacteria. Lactobacillus bulgaricus synthesized AgNPs tested via disc diffusion method. AgNPs demonstrated strong antibacterial effects without cytotoxicity at 1.5 mg/ml. Keywords: A Silver nanoparticles, Lactobacillus bulgaricus, pathogenic strains